2014
DOI: 10.5194/bg-11-4521-2014
|View full text |Cite
|
Sign up to set email alerts
|

Have ozone effects on carbon sequestration been overestimated? A new biomass response function for wheat

Abstract: Abstract. Elevated levels of tropospheric ozone can significantly impair the growth of crops. The reduced removal of CO 2 by plants leads to higher atmospheric concentrations of CO 2 , enhancing radiative forcing. Ozone effects on economic yield, e.g. the grain yield of wheat (Triticum aestivum L.), are currently used to model effects on radiative forcing. However, changes in grain yield do not necessarily reflect changes in total biomass. Based on an analysis of 22 ozone exposure experiments with field-grown … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…One possible explanation could involve a shift in partitioning of photosynthate among various plant parts, roots, shoots, foliage, etc. (Rennenberg et al 1996;Pleijel et al 2014). Another explanation is that insensitive grasses appear to fill niches left as the level of the clover falls, similar to the report of Gonzalez-Fernandez et al (2008), who found that ryegrass (L. perenne) replaced clover when the two were grown simultaneously under elevated ozone concentrations.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…One possible explanation could involve a shift in partitioning of photosynthate among various plant parts, roots, shoots, foliage, etc. (Rennenberg et al 1996;Pleijel et al 2014). Another explanation is that insensitive grasses appear to fill niches left as the level of the clover falls, similar to the report of Gonzalez-Fernandez et al (2008), who found that ryegrass (L. perenne) replaced clover when the two were grown simultaneously under elevated ozone concentrations.…”
Section: Discussionsupporting
confidence: 70%
“…; Pleijel et al . ). Another explanation is that insensitive grasses appear to fill niches left as the level of the clover falls, similar to the report of Gonzalez‐Fernandez et al .…”
Section: Discussionmentioning
confidence: 97%
“…Yield losses due to ozone have been ascribed to various yield components in different crops, including reductions in individual seed weight, reduced spikelet number, enhanced spikelet fertility, and reduced panicle or pod number (Ainsworth, 2008;Feng, Kobayashi, & Ainsworth, 2008;Morgan, Ainsworth, & Long, 2003), with associated reductions in harvest index (e.g. for wheat, Pleijel, Danielsson, Simpson, & Mills, 2014). Maintaining high values in these harvest fractions despite ozone stress forms an important breeding target, but synergies or trade-offs with other types of stress would be complex and little information is available to date.…”
Section: Plant Traits Associated With Tolerance Of Ozone and Associmentioning
confidence: 99%
“…That sensitivity implies a 20 %-24 % drop in biomass production at FLUXNET crop sites. Some studies have quantified O 3 dose-response relationships with other thresholds Y = 1.6 to 6 nmol O 3 m −2 s −1 (e.g., Karlsson et al, 2007;Pleijel et al, 2004Pleijel et al, , 2014, but the sensitivities have a similar magnitude. Fares et al (2013) also demonstrated 12 %-19 % reduction in gross primary production due to O 3 at some of the same crop and forest FLUXNET sites.…”
Section: W126mentioning
confidence: 99%